Caso clínico: síndrome de Baboon secundario a cuerpo extraño cutáneo - Saavedra U. , Tirza; Valenzuela A., Fernando; Wortsman C., Ximena; Carreño T., Laura (Revista Hospital Clínico Universidad de Chile, 2008)
We report the clinical case of a 12 year-old healthy pediatric patient with a history of allergic contact dermatitis to nickel. He presented a papular symmetrical scarlatiniform rash after a gunshot impact partially withdrawn that began mainly in folds, which generalized to the rest of the body. We performed high-resolution ultrasonography in the impact area showing multiple small particles around a fibrous scar. The skin biopsy was consistent with systemic contact dermatitis, and immunofluorescence resulted negative. He was treated with prednisone for 5 days and anti-TNF antihistamines with good results. Nickel contact dermatitis is common inclinical practice, but systemic contact dermatitis is less frequent and even less because of a foreign body, although it has already been described. The Baboon syndrome is a maculopapular itchy rash that begins in folds and then generalizes, one of its etiologies is nickel, it should be a type IV hypersensitivity that resolves spontaneously without scars.